Laboratories of social innovation, as a strategy for the strengthening of citizen participation [Laboratorios de innovación social, como estrategia para el fortalecimiento de la participación ciudadana] (2019)
The present article approaches elements of the design of a laboratory of social innovation from the Faculty of Social Sciences of the Greater School of Antioquia in the city of Medellin-Colombia, with the purpose of generating a space that promotes the cocreacion to solve social problems, by means of the application of innovation and technology processes for social appropriation, which allows connecting, more and more, the university with the community, where the strategies of university practices, extension and social projection, and civil society converge. The focus of the research is qualitative and contemplates a phenomenological design with interview techniques with alternative didactic approaches such as Participation Action Research. As a result, the most representative elements of the bibliographic review carried out on the social innovation laboratory are presented, as well as the interviews and panels with experts carried out, which show the importance that these spaces take in the development of the communities, starting from Public efforts calling them citizen laboratories or public innovation, promoting the strengthening of collaboration networks between different agents of society. It concludes with the importance of initiating the pilot test in a Higher Education Institution. © 2019 Universidad del Zulia.